VIM-encoding IncpSTY plasmids and chromosome-borne integrative and mobilizable elements (IMEs) and integrative and conjugative elements (ICEs) in Pseudomonas - Fangzhou Chen; Peng Wang; Zhe Yin; Huiying Yang; Lingfei Hu; Ting Yu; Ying Jing; Jiayao Guan; Jiahong Wu; Dongsheng Zhou (BMC, 2022)
Abstract Background The carbapenem-resistance genes bla VIM are widely disseminated in Pseudomonas, and frequently harbored within class 1 integrons that reside within various mobile genetic elements (MGEs). However, there are few reports on detailed genetic dissection of bla VIM-carrying MGEs in Pseudomonas. Methods This study presented the complete sequences of five bla VIM-2/-4-carrying MGEs, including two plasmids, two chromosomal integrative and mobilizable elements (IMEs), and one chromosomal integrative and conjugative element (ICE) from five different Pseudomonas isolates. Results The two plasmids were assigned to a novel incompatibility (Inc) group IncpSTY, which included only seven available plasmids with determined complete sequences and could be further divided into three subgroups IncpSTY-1/2/3. A detailed sequence comparison was then applied to a collection of 15 MGEs belonging to four different groups: three representative IncpSTY plasmids, two Tn6916-related IMEs, two Tn6918-related IMEs, and eight Tn6417-related ICEs and ten of these 15 MGEs were first time identified. At least 22 genes involving resistance to seven different categories of antibiotics and heavy metals were identified within these 15 MGEs, and most of these resistance genes were located within the accessory modules integrated as exogenous DNA regions into these MGEs. Especially, eleven of these 15 MGEs carried the bla VIM genes, which were located within 11 different concise class 1 integrons. Conclusion These bla VIM-carrying integrons were further integrated into the above plasmids, IMEs/ICEs with intercellular mobility. These MGEs could transfer between Pseudomonas isolates, which resulted in the accumulation and spread of bla VIM among Pseudomonas and thus was helpful for the bacteria to survival from the stress of antibiotics. Data presented here provided a deeper insight into the genetic diversification and evolution of VIM-encoding MGEs in Pseudomonas.